Design and Development of an E-commerce Application Using the Web Information System Development Methodology - Hadi, Wahyu Nofiyan; Latifah, Ummi; Susilowati, Umi Diantika; Wilda, Anisa Nurul; Fadel, Moh. (Journal of Electrical Engineering and Computer (JEECOM), 2025)
The main objective of this research is to design and build an e-commerce application to enhance the competitiveness of micro, small, and medium enterprises in Sumbertaman, Probolinggo City. In the development process, the Web Information System Development Methodology (WISDM) method was used, which consists of the stages of needs analysis, design, implementation, testing, and evaluation. This research began with data collection through interviews and direct observations of local micro, small, and medium enterprises to understand the specific needs related to the e-commerce system. The research results show that the developed application is capable of meeting the needs of micro, small, and medium enterprises in terms of product management, sales transactions, and real-time data reporting. The implementation of this application is expected to provide convenience for micro, small, and medium enterprises to market their products online, improve operational efficiency, and expand market reach. Thus, this WISDM-based e-commerce application significantly contributes to the digitalization of local businesses in the era of digital transformation.